NATURAL RESOURCES AND SUSTAINABLE DEVELOPMENT IN A MOUNTAIN ECONOMY - Jelev, Viorica (Annals of Spiru Haret University. Economic Series, 2018)
This paper presents the existing situation at national and world level considering the available water resources, their vulnerability especially in the mountains areas, the impact of climate changes, the possible conflicts regarding the intensification of water shortage in some regions of the world. I also present a case study on forests in Romania. Beginning with the general data mentioned above, we point out the specific peculiarities of the mountain area hydrology for identifying some aspects which are specific to the mountain water relationship. The analysis is necessary as no specifications regarding the mountain hilly or plain areas are done in the activity regarding waters management. Waters are managed unitary on river basins considering some general principles, unanimously recognized, well reflected into the national and international regulations. As a first stage, traditional economic activities are identified in the relationship of the mountain areas inhabitants with water but also some present approaches. The way the mountain areas inhabitants knew how to live together and capitalize water resources represents a model and impulse for coming back to such sustainable solutions but capitalizing the advantages of modern technologies. Each of these activities referring to waters which take place in the mountains area can represent ways for the research activity and future thorough studies from the technical, economic, social, cultural-traditional point of view and also for environment protection. A main preoccupation might have connection with the evolution of agricultural activities in the mountains area considering the climate changes and a possible “migration” towards higher areas of some agricultural practices specific to lower areas. The paper also shows a small example of the regaining by the locals of a community of an important resource for their lives in the hands of corporations: the forests defaced by HOLZINDUSTRIE SCHWEIGHOFER and stop flooding villages.